MINDFULNESS, WORK-LIFE BALANCE, AND PSYCHOLOGICAL WELL-BEING IN WORKING MOTHER - Novenia, Deya; Wibhowo, Christin (Universitas Mercu Buana Jakarta, 2024)
Being a working mother is not easy because she must be able to share the roles equally. The best condition that a working mother can achieve in order to be able to carry out her role is to have psychological well-being which illustrates that a healthy mental state will affect various aspects of life. The purpose of this study was to determine the correlation between mindfulness, work-life balance, and psychological well-being in working mother. Participants in this study were working mother aged 25-54 years, full time employee in corporate or office, married, have children, and live in Semarang. This study using accicental sampling technique with a sample of 80 people. The research data were taken using psychological well-being scale, five facet mindfulness questionnaire, and work-life balance scale. Data were analyzed using multiple linear regression analysis. From the results of these studies, it can be concluded that the hypotheses in this study were accepted. This research can be used as additional information for working mother regarding the factors that influence their psychological well-being so that they can carry out their various roles to the fullest